"Die skurwe liefde om te besit": teologiese riglyne vir sake-etiek - L. O. K. Lategan (Acta Theologica)
This article points out the importance of business ethics and the guidelines needed by Christian business people for participating in business activities. For this reason theological guidelines are provided for business activities. Section 2 focuses on three key concepts, namely man as manager of God’s property; the central love command and the religious conviction of man. Section 3 argues that no business ethics can exist without understanding the role of compromise in daily life. Section 4 discusses two case studies against the background of values for business ethics. The article concludes with three important guidelines for business ethics.